2015
DOI: 10.29065/usakead.232402
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’de Vatandaşlık Eğitimi Üzerine Bir İnceleme

Abstract: Bu çalışmada, Türkiye'de ilk ve ortaöğretim seviyesinde vatandaşlık eğitiminin, öğretim programı, okulda öğrenci ve veli katılımı, öğrencinin topluma katılımı, ölçme ve değerlendirme, öğretmen ve müdürlere destek sağlama boyutları altında incelenmesi amaçlanmıştır. Konu ile ilgili yapılmış bilimsel araştırmaların sonucunda elde edilen temel bulgular incelenmiş ve sunulmuştur. Çalışmanın sonucunda; vatandaşlık eğitiminin 2014-2015 eğitim-öğretim yılı itibariyle ilköğretim 4. sınıfta zorunlu bir ders olarak okut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
6
0
5
Order By: Relevance
“…As Child-to-Child approach encourages the active participation of students in the teaching and learning process by providing them with the opportunity to take actions in the community, students could contribute to the solution of social problems in their school and the community. Several researchers (e.g., Akşit, 2009;Ersoy, 2014;Keser et al, 2011;KaramanKepenekci, 2005;Mısırlı-Özsoy, 2010;Som & Karataş, 2015;Şensoy, 2014;Ülger, 2013) also underline the positive impact of authentic and extra-curricular activities on the development of active citizenship and the promotion of active citizenship values and competencies in Turkish schools. In particular, as Keser et al (2011) argue, these extra-curricular activities enable students to develop an active citizenship perception, social accountability, intercultural awareness, awareness of democracy and human rights, thinking and research skills, and interaction and intrapersonal skills which comply with the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Child-to-Child approach encourages the active participation of students in the teaching and learning process by providing them with the opportunity to take actions in the community, students could contribute to the solution of social problems in their school and the community. Several researchers (e.g., Akşit, 2009;Ersoy, 2014;Keser et al, 2011;KaramanKepenekci, 2005;Mısırlı-Özsoy, 2010;Som & Karataş, 2015;Şensoy, 2014;Ülger, 2013) also underline the positive impact of authentic and extra-curricular activities on the development of active citizenship and the promotion of active citizenship values and competencies in Turkish schools. In particular, as Keser et al (2011) argue, these extra-curricular activities enable students to develop an active citizenship perception, social accountability, intercultural awareness, awareness of democracy and human rights, thinking and research skills, and interaction and intrapersonal skills which comply with the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…As Çayır (2002) suggests, an effective citizenship education needs to promote inquiry and action with the aim of creating behavioral and attitudinal changes rather than limiting itself to the cognitive domain. To this end, the use of teamwork, role-playing, visual aids, activity-based scenarios, problem-based learning, school trips, and case studies are widely recommended (Çayır, 2002;Som & Karataş, 2015) which basically enable students to be active in the learning process and provide them with the opportunity to practice active citizenship in the real life (Sadık & Sarı, 2012). For teaching citizenship at school, Scheerens (2011) talks about two distinct methods which are "the context embedded approach" and "the explicit teaching approach."…”
Section: Discussionmentioning
confidence: 99%
“…Bu sebeple, Türkiye'de vatandaşlık eğitiminin, hâlen sıkı bir şekilde geleneksel vatandaşlık kavramını temel aldığı eleştirilmekte ve bireylere çağın gerektirdiği vatandaşlık bilgisi ve becerilerini kazandırmak üzere aktif vatandaşlık kavramının gelişmesi için mevcut koşul ve olanakların yeterli olmadığı vurgulanmaktadır (Keser ve diğerleri, 2011). Bunun bir sonucu olarak, alanyazındaki birçok araştırmadan elde edilen bulgular vatandaşlık eğitiminde öğretim programları ve ders kitapları ile ilgili problemler olduğunu ortaya koymakta (örn., Bıçak ve Ereş, 2018;Caymaz, 2008;Çayır, 2009Çayır ve Bağlı, 2011;Çayır ve Gürkaynak, 2008;Ersoy, Balbağ ve Gündoğan-Bayır, 2017;İnce, 2012;Karakuş-Özdemirci, Aksoy ve Ok, 2020;Karaman-Kepenekci, 2005;Memişoğlu, 2014;Merey, Karatekin ve Kuş, 2012;Sen, 2019;Sen ve Starkey, S. Akın / Pamukkale Üniversitesi Eğitim Fakültesi Dergisi, XX, SS-SS, 2021 4 2017; Som ve Karataş, 2015;Şen, 2019); öğretmenlerin aktif vatandaşlıkla ilgili sınırlı bilgi, beceri, tutum ve algıya sahip olduğunu ve yeterli pedagojik bilgilerinin olmadığını belirtmekte (örn., Çayır ve Bağlı, 2011;Ersoy, 2014a;Eryılmaz, Bursa ve Ersoy, 2018;Kuş ve Aksu, 2017;Memişoğlu, 2014;Öztürk, Malkoç ve Ersoy, 2016); benzer şekilde farklı eğitim kademelerindeki öğrencilerin de aktif vatandaşlıkla ilgili yeterli bilgi, beceri, tutum ya da algı geliştiremediğini tartışmaktadır (örn., Bağlı, 2013;Baloğlu-Uğurlu, 2013;Çayır ve Bağlı, 2011;Ersoy, 2014a;Eryılmaz ve diğerleri, 2018).…”
Section: Aktif Vatandaşlıkunclassified
“…Whether citizenship education should be given as a separate course or should be included in each course has been the subject of discussion. Som and Karataş (2015) argue that citizenship education should be integrated into other courses rather than being given as a separate course. Martin (2010), in his research, concluded that citizenship education could be taught through interdisciplinary or non-interdisciplinary methods in school processes.…”
Section: Citizenship Educationmentioning
confidence: 99%
“…In this context, it can be said that the meanings attributed by the participants to the concepts of citizenship and citizenship education coincide with the definitions of the concept in the literature, and they are similar to those of different research findings. Som and Karataş (2015) state that students should participate actively in the process of citizenship education, and teaching methods should be employed together with knowledge, skills, and values, and the curriculum should be prepared in this context. In this study, all the participants had conducted studies on citizenship knowledge and skills in the teaching processes, and took into account the content of the curriculum.…”
Section: Curriculum-oriented Factors Affecting the Development Of Citizenshipmentioning
confidence: 99%